Ligature induced periodontitis causes atherosclerosis in rat descending aorta: an experimental study - Dimitriu, Tudor; Bolfa, Pompei; Daradics, Zsofia; Suciu, Șoimița; Cătoi, Cornel; Armencea, Gabriel; Dinu, Cristian; Băciuț, Grigore; Văcăraș, Sergiu; Bran, Simion; Băciuț, Mihaela (Medicine and Pharmacy Reports, 2021)
Introduction. In recent years a link between periodontitis and cardiovascular diseases has been proposed. Oxidative stress has been found to be involved in their pathophysiology. Objectives. The aim of this study was to demonstrate that a wire ligature placed around the first mandibular molars of the rat causes inflammation in the periodontium and lipid deposits in the aorta, via oxidative stress. Methods. Twenty male Wistar rats were divided randomly into two groups of 10: Control group and Periodontitis group. An orthodontic wire ligature was placed around the cervix of the first mandibular molar and was kept in place for 4 weeks. Clinical attachment loss was determined to assess the gingival recession. Aorta was harvested after 4 weeks and the malondialdehyde (MDA) levels in the aorta tissue homogenate were determined. Lipid deposits were evaluated using Oil Red staining and immunofluorescence under confocal microscopy. Total lipid deposits in the aorta were assessed using a computer morphometry system. Results. Significant gingival recession was observed in the Periodontitis group in comparison with the Control group. Increased MDA levels were present in the aorta in the ligatured rats in comparison with the Control group. Significant lipid deposits were observed in the aorta of the Periodontitis group as opposed to the Control group. Conclusions. The affixing of an orthodontic wire ligature produces gingival recession, increased oxidative stress and lipid deposits in the rat descending aorta.